Pengaruh Kombinasi Pupuk NPK dan Batubara terhadap Ketersediaan Fosfor pada Lahan Pasang Surut - Rahman Hidayat; Fakhrur Razie; Ratna . (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2024)
Problems faced in tidal swamp land include low soil pH, low nutrient content, and high levels of Al and Fe. The aim of this research was to determine the effect of the combination of NPK fertilizer and Futura coal fertilizer on the availability of P and to determine the relationship between the solubility of Al and Fe, pH and organic C on the availability of P in tidal swamp land. This research was carried out at the Chemistry Laboratory, Soil Department, Faculty of Agriculture, Lambung Mangkurat University from October-December 2023 using a single factor in Randomized Block Design with five treatments and three replications to obtain 15 experimental units. The combination of NPK and Futura increased the availability of P, organic-C, and soil pH and reduced the solubility of Al and Fe. A relationship was found between Al and soil pH, C-organic and Al, C-organic and soil pH, organic-C and soluble-Fe, soluble-Fe and soil pH.